Resepsi Al-Qur’an di Media Sosial (Studi atas Pengamalan QS. Yūsuf/12: 4 di Tiktok) - Sari Silviani; Akbar Akbar (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2023)
Performances of the Qur’an that appear irrelevant to authoritative interpretation discourses, such as the practise of QS. Yūsuf: 4 by a number of Tiktok users, can occasionally be found on social media. This qualitative study employs a field research design to examine these trends by observing and interviewing five Tiktok users as data sources. The researcher describes how Tiktok users practise QS. Yūsuf/12: 4 and investigates its relationship with the function of the verse’s meaning, as well as analyses the motives and sources of their behaviour using the Qur’an Reception approach. According to the findings of the study, Tiktok users perceive QS. Yūsuf/12: 4 functionally with various practises and utilising a variety of media to obtain submission, obedience, appreciation, and even love from the party he desires. This motivation stems from their understanding of the meaning of the phrase “lī sājidīn” in the verse. They claim that such acceptance refers to various interpretive sources as well as formal and informal teachers. Despite the fact that there is a semantic correlation between practise and the meaning of the verse, the intent, purpose, and message of the Prophet Yusuf's story are not represented in their practise. The rise of social media information has influenced this phenomenon, reinforcing the lack of interpretation literacy. The performance of social media users who are dominated by simplistic theological readings must be coloured by strengthening interpretation literacy and authoritative sources so that the dimension of worship in practising the Qur’an is more scientific and can be developed professionally